Social Networks, the Tertius Iungens Orientation, and Involvement in Innovation - Obstfeld, David (Administrative Science Quarterly, 2005)
This study examines the microprocesses in the social networks of those involved in organizational innovation and their strategic behavioral orientation toward connecting people in their social network by either introducing disconnected individuals or facilitating new coordination between connected individuals. This tertius iungens (or “third who joins”) strategic orientation, contrasts with the tertius gaudens orientation emphasized in structural holes theory, which concerns the advantage of a broker who can play people off against one another for his or her own benefit. Results of a multimethod study of networks and innovation in an engineering division of an automotive manufacturer show that a tertius iungens orientation, dense social networks, and diverse social knowledge predict involvement in innovation. Implications of the study for innovation and social networks, as well as for social skill and agency within firms are presented.